DETERMINANTS OF URBAN FARMING INCOME IN YOGYAKARTA: AN EMPIRICAL ANALYSIS OF OPERATIONAL, BIOTIC STRESS, AND INSTITUTIONAL FACTORS - Hedwig Ajeng Grahani (Universitas Sebelas Maret (UNS), 2026)
Although Indonesia's metropolitan districts are seeing fast economic expansion, urban residents are nonetheless at risk because of unstable income and few job prospects. Urban poverty and unemployment rates in Yogyakarta's Special Region are still comparatively high, highlighting the need for alternative livelihood methods. Although urban farming has become a supplementary source of income to increase household resilience, the factors influencing its income performance are still unclear. The purpose of this study is to examine the structural, operational, biotic, and institutional aspects of urban farming revenue in Yogyakarta City. In 2024, a systematic questionnaire was used to gather primary data from 217 urban farming households. Stata 19 was used for hypothesis testing, and SPSS 27 was used for descriptive analysis. Net urban farming income was the dependent variable in a multiple linear regression model, and 22 independent variables were used to indicate sociodemographic traits, farm structure, input management, biotic stress, and institutional support. Eleven variables have a significant impact on income, and the results demonstrate excellent explanatory power (R2 = 0.7448). The most favorable factor is farm size, which is followed by financial support, seed subsidies, and technical aid. Positive impacts also come from gender and family size, emphasizing the importance of women's involvement and domestic work. Crop type has a negative correlation with income, although fertilizer type and expenditure boost it. Income is greatly decreased by biotic stress, particularly pest type and severity. The variables of training and market access are not statistically significant. In Yogyakarta, land access, household labor, efficient input usage, pest and disease control, and institutional assistance are the main factors influencing urban farming income.